Effect Of Maturity Level Of Kepok Banana (Musa paradisiaca formatypica) On Chemical And Organoleptic Properties Of Frozen Fried Banana - Maria Anastasia Ferida Bura; Maya M. Ludong; Yoakhim Y.E. Oessoe (Sam Ratulangi University, 2023)
This study aims to determine the maturity level of good kepok bananas in the manufacture of frozen fried bananas. Based on chemical characteristics (moisture content, fat content, total sugar), and organoleptic. This study used a factorial complete randomized design (RAL) which consisted of 4 treatments: P1 treatment, namely kepok bananas with a maturity level of 3 (yellowish green), P2 treatment, namely kepok bananas with a maturity level of 4 (more yellow than green), P3 treatment, namely kepok bananas with a maturity level of 5 (yellow with green tips), P4 treatment, namely kepok bananas with a maturity level of 6 (full yellow). The parameters analyzed were water content, fat content, total sugar and organoleptic which included taste and texture. The organoleptic test results of frozen fried bananas in the second frying pan which were the most preferred by the panelists in terms of taste and texture were the P4 treatment, namely full yellow ripeness level 6 bananas had good organoleptic, with chemical characteristics (44.50% moisture, 36.64% fat , and total sugar 40.81%). Keywords : Banana Kepok, Frozen Fried Banana, Banana Maturity Level. Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kematangan pisang kepok yang baik dalam pembuatan pisang goreng beku. Berdasarkan sifat kimia (kadar air, kadar lemak, gula total), dan organoleptik. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) faktorial yang terdiri dari 4 perlakuan yaitu perlakuan P1 yaitu pisang kepok dengan tingkat kematangan 3 (hijau kekuningan), perlakuan P2 yaitu pisang kepok dengan tingkat kematangan 4 (lebih kuning dari hijau), perlakuan P3 yaitu pisang kepok dengan tingkat kematangan 5 (kuning berujung hijau), perlakuan P4 yaitu pisang kepok dengan tingkat kematangan 6 (kuning penuh). Parameter yang dianalisis adalah kadar air, kadar lemak, gula total dan organoleptik yang meliputi rasa dan tekstur. Hasil uji organoleptik pisang goreng beku pada penggorengan kedua yang paling disukai panelis dari segi rasa dan tekstur adalah perlakuan P4 yaitu pisang tingkat kematangan full yellow 6 memiliki organoleptik yang baik, dengan karakteristik kimiawi (kelembaban 44,50%). ), lemak 36,64%, dan gula total 40,81%). Kata kunci : Pisang kepok, Pisang Goreng Beku, Tingkat Kematangan Pisang